The prognostic and diagnostic value of intraleukocytic malaria pigment in patients with severe falciparum malaria - Srinamon, K; Watson, JA; Silamut, K; Intharabut, B; Phu, NH; Diep, PT; Lyke, KE; Fanello, C; von Seidlein, L; Chotivanich, K; Dondorp, AM; Day, NPJ; et al. (Springer Nature, 2022)
Severe falciparum malaria is a major cause of death in tropical countries, particularly in African children. Rapid and accurate diagnosis and prognostic assessment are critical to clinical management. In 6027 prospectively studied patients diagnosed with severe malaria we assess the prognostic value of peripheral blood film counts of malaria pigment containing polymorphonuclear leukocytes (PMNs) and monocytes. We combine these results with previously published data and show, in an individual patient data meta-analysis (n = 32,035), that the proportion of pigment containing PMNs is predictive of in-hospital mortality. In African children the proportion of pigment containing PMNs helps distinguish severe malaria from other life-threatening febrile illnesses, and it adds to the prognostic assessment from simple bedside examination, and to the conventional malaria parasite count. Microscopy assessment of pigment containing PMNs is simple and rapid, and should be performed in all patients hospitalised with suspected severe malaria.